GERAKAN TAHRIRUL MAR’AH DAN FEMINISME (STUDI TERHADAP KESETARAAN GENDER DALAM ISLAM) - Hamidah Hamidah (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
Feminism movement generally understood as an effort to self-liberation of women from a variety of inequality of treatment in all aspects of community life. Along with the presence of feminism in the West, in the Islamic world there are also women's movement, known as Tahrirul mar'ah. Between feminism and tahrirul mar'ah have the same elements, namely the struggle to free women from a subordinate position, refresif and marginal heading on a balanced position. Mar'ah tahrirul presence is indispensable to the feminist movement in the Western world. In fact it can be assumed that women's movements that developed in Islamic countries is the influence of feminism in the West, although this is not to circumvent the internal dynamics of Muslim women themselves. In understanding the concept of gender equality, the second movement has a different frame. Some verses in the Qur'an and hadith that explains about gender equality.